High-frequency repetitive transcranial magnetic stimulation alleviates the cognitive side effects of electroconvulsive therapy in major depression - Chen, Xing; Zhang, Tongtong; Shan, Xiaoyan; Yang, Qun; Zhang, Peiyun; Zhu, Haijiao; Jiang, Fei; Liu, Chao; Li, Yanzhong; Li, Weijun; Xu, Jian; Shen, Hongmei (Frontiers in Psychiatry, 2022)
Objective: The retrospective study aimed to explore the difference in mood outcomes and cognitive function between high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) over dorsolateral prefrontal cortex (DLPFC) and electroconvulsive therapy in major depression disorder (MDD) patients, and examine the improvement of HF-rTMS on cognitive impairment evoked by ECT. Methods: A total of 116 participants with MDD, completed a 4-week follow-up assessment, were enrolled. The cohort consisted of 26 cases classed as control, 46 participants administrated with HF-rTMS (HF-rTMS group), 22 patients treated with ECT (ECT group), and 23 cases treated with HF-rTMS and ECT at the course of hospitalization (HF-rTMS + ECT group). Medication was kept constant as well in all participants. The 17-item Hamilton Depression Rating Scale for Depression (HAMD-17) and 14-item Hamilton Anxiety Rating Scale (HAMA-14) were used to assess depression and anxiety, respectively. Montreal Cognitive Assessment (MoCA) was to elevate cognitive function. Results: No statistical significance was found for baseline in sociodemographic, characteristics of depression, anxiety and cognition, and psychopharmaceutic dosages among control, HF-rTMS, ECT, and HF-rTMS + ECT groups (p > 0.05). Compared with baseline level, total scores of HAMD-17 and HAMA-14 significantly decreased at end of four weeks after treatment (p < 0.001). Furthermore, the decline in scores of HAMD-17 and its sleep disorder and retardation factors from baseline to post-treatment was greater in HF-rTMS, ECT, and HF-rTMS + ECT group than in control (p < 0.05), and there was a significant difference between control and HF-rTMS group in the decline of psychological factor of HAMA-14 (p < 0.01). ECT treatment evoked total score of MoCA decreased significantly at the end of 4-week after intervention (p < 0.001), and the decline in scores of MoCA and its delayed recall and language performances from baseline to post-treatment was greater in ECT than control, HF-rTMS, and HF-rTMS + ECT (p < 0.05). Conclusion: HF-rTMS improved psychological anxiety and ameliorated the cognition impairment evoked by ECT though it had the same antidepressant efficacy as ECT.